Urban Growth During Civilian and Military Administrations in Osogbo, Nigeria - Olalekan John Taiwo (Indonesian Journal of Geography, 2018)
Research on comparative analysis of urban growth and structure during military and civilian regimes most especially in Africa where coup d’etats is common and where private individuals mainly control land is limited. This study analyzed the temporal patterns and morphological characteristics of urban growth during the military and civilian regimes as well as during different civilian administrations using eight landscape metrics. Landsat satellite images of 1984, 1991, 2000, 2003, 2010 and 2014 were used in the analysis. It was found that urban growth occurred primarily through expansion (annexation) of extant urban areas rather than spontaneous and detached development.